James A. Stewart, 1918. - Ideal Studio (Forsyth County Public Library, 1918)
Source: Booklet, "Winston-Salem, City of Industry," 1918.
James A. Stewart, 1918. Mr. Stewart operated a fruit and confectionery business.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth